the Short Abstinence May Have Paradoxical Effects On Sperms With Different Level Of DNA Integrity: A Prospective Study - Vahidi, Serajeddin; Narimani, Nima; ghanizadeh, Taha; Yazdinejad, Fatemeh; Emami, Maryam; Mehravaran, Kaveh; Saffari, Hossein; Khaleghimehr, Farhood; Dehghan Marvast, Laleh (Urology Journal, 2021)
Purpose: To investigate the effect of short abstinence on sperm function tests and semen parameters. Materials and methods: This prospective study included 65 male patients with increased DNA injury in their ejaculated sperm and a history of recurrent pregnancy loss and/or assisted reproductive techniques failures. The effects of antioxidants medical therapy and short abstinence on semen quality were assessed (TUNEL test and CMA3 staining). Results: Antioxidants have statistically significant effects on mean sperm concentration (untreated, 67.51 ± 44.40 million/ml, vs. treated, 56.09 ± 37.85 million/ml; P-value=0.005) and mean TUNEL score (untreated, 24.56% ± 9.49%, vs. treated, 20.64% ± 10.28%; P-value = 0.013). Moreover, a short abstinence period might have positive effects as shown on the TUNEL assay (20.64% ± 10.28 vs. 17.38% ± 8.59 ; P-value = 0.028) and CMA3 staining (47.79% ± 20.78, vs. short 41.92% ± 18.49; P-value = 0.019), when considering all study subjects. However, different results were obtained using more precise analysis based on a TUNEL cutoff score of 20%. The analysis showed that short abstinence might improve sperm DNA integrity in patients with TUNEL score > 20% (mean TUNEL score from 27.85% ± 8.32% to 19.14% ± 8.90% ; P-value =0.001%). However, it might have deleterious effects on sperm DNA integrity in patients with TUNEL score < 20% (mean TUNEL score from 11.89% ± 3.21% to 15.17% ± 7.79%; P-value = 0.045%) Conclusion: Our results showed that short abstinence may not be beneficial in all infertile males, and it should only be used in selected patients with abnormal DNA integrity.